Glutamine addiction: an Achilles heel in esophageal cancers with dysregulation of CDK4/6. (4th July 2019) - Qie, Shuo; Diehl, J. Alan
ABSTRACT: Understanding and overcoming resistance to cyclin-dependent kinase 4/6 (CDK4/6) inhibitors will be challenging. Recent work reveals that dysregulation of F-Box Protein 4 (FBXO4)-Cyclin D1 axis leads to mitochondrial dysfunction and drives glutamine-addiction in esophageal squamous cell carcinoma. This metabolism feature makes these tumors susceptible to combined treatment with glutaminase (GLS) inhibitor and metformin even when resisting to CDK4/6 inhibitors.